AKTUALISASI PAHAM KEADILAN ISLAM TERHADAP DOKTRIN MADZHAB KEKUASAAN HUKUM MODERN - Aristoni Aristoni; Fifi Nofiaturrahmah (Program Studi Hukum Keluarga Islam, 2015)
In the modern context, legal doctrine is often positioned as a perfect value. This attitude positioned legal doctrine as absolute and people will not be able to evaluate. Civil law and common law as a modern school of law consider this condition as the position to implement concept of justice. Islam has offered a different form of justice. In Islam, justice is not only about socio-religious rites but also the implementation of syariat and haqiqat by Indonesian Muslims. The concept of justice in Islam can be different from those of civil and common law. Justice in Islam is more in the equity of legal procedures and substantive character as the core of legal justice.